Effects of Precursor Structure on First-Generation Photo-Oxidation Organic Aerosol Formation - Sofio, D.; Long, D.; Kohls, T.; Kunz, J.; Wentzel, M.; Hanson, D. (Frontiers in Environmental Science, 2022)
The effect of molecular structural features on secondary organic aerosol (SOA) growth was investigated via changes in precursor functional groups. SOA yields were determined for straight chain alkanes, some oxygenated, up to highly functionalized hydrocarbons ending with β-caryophyllene. Organic SOA yield was determined by comparing to standard particle size changes with SO2 in a photolytic flow reactor. SOA formation was initiated with OH radicals from HONO photolysis and continued with NO and NO2 present at single-digit parts per billion levels. Seed particle of ~ 10 nm diameter grew by condensation of SOA material and growth was monitored with a nanoparticle sizing system. Cyclic compounds dominate as the highest SOA yielding structural feature, followed by C-10 species with double bonds, with linear alkanes and isoprene most ineffective. Carbonyl-containing alkanes led to significant increases in growth compared to the alkanes while alcohols, triple-bond compounds, aromatics, epoxides, were only slightly more effective than the alkanes at producing SOA. When more than one double bond is present, or a double bond is present with another functional group as seen with 1, 2-epoxydec-9-ene, SOA yield is notably increased. Placement of the double bond is important as well with -pinene having an SOA yield approximately 5 times that of -pinene. In our photolytic flow reactor, first-generation oxidation products are presumed to be the primary species contributing to SOA thus the molecular structure of the precursor is determinant. We also conducted proton-transfer mass spectrometry measurements of -pinene photooxidation and significant signals were observed at masses for multifunctional nitrates and peroxy radicals. The mass spectrometer measurements were also used to estimate a HONO photolysis rate.